Calculation of temperature distribution and rheological properties of the lithosphere along transect IV in the Western Carpathian-Pannonian Basin region - DÉREROVÁ, Jana; BIELIK, Miroslav; KOHÚT, Igor; GODOVÁ, Dominika (Contributions to Geophysics and Geodesy, 2019)
2D integrated modelling algorithm was used to calculate the temperature distribution in the lithosphere along the transect IV located in the Western Carpathian-Pannonian Basin area. Based on the determined temperature field and given rheological parameters of the rocks, it was possible to calculate the strength distribution for both compressional and extensional regimes, construct the strength envelopes for chosen columns ofthe main tectonic units of the model, and thus construct a simple rheological model of the lithosphere along transect IV. The obtained results indicate decrease of the lithospheric strength from the European platform and the Western Carpathians towards the Pannonian Basin. The largest strength (valid for all tectonic units) can be observed within the upper crust with its maxima on the boundary between upper and lower crust, decreasingtowards lower crust and disappearing in the lithospheric mantle, suggesting mostly rigid deformation occurring in the upper crust. A local increase in the values of strength can be observed in the eastern segment of the Western Carpathians where crustal thickening accompanies the lithospheric thickening (formation of the lithospheric root), unlike the previous models along transects I and II, that pass through the western segment of the Western Carpathians and their lithosphere-asthenosphere boundary is almost flat and therefore no accompanying crustal thickening is observed and the decrease in strength is slow and steady.